Analysis of Presentation and Disclosure of Tax Amnesty Assets and Liability in the Financial Statements of Listed Public Company in Indonesia - Martani , Dwi; Maharani, Ayu (KnE Social Sciences, 2020)
The purpose of this study is to analyze the implementation and consistency of the presentation and disclosure of tax amnesty assets and liabilities based on PSAK 70 about Accounting for Tax Amnesty Assets and Liabilities. This study uses content analysis and focuses on companies participating in tax amnesty based on Law No. 11 of 2016 concerning Tax Amnesty. Companies that participate in tax amnesty need to adjust their accounting policies to present and disclose tax amnesty assets and liabilities. The presentation and disclosure options are carried out consistently for all tax amnesty assets and liabilities. The analysis showed that the company consistently presents its tax amnesty assets and liabilities according to the options selected in PSAK 70. However, the completeness of disclosure of tax amnesty elements in the financial statements was relatively diverse. Keywords: tax amnesty, tax amnesty assets, tax amnesty liabilities